2015
DOI: 10.1007/s10832-015-9988-7
|View full text |Cite
|
Sign up to set email alerts
|

High conductivity of mixed phase Al-substituted Li7La3Zr2O12

Abstract: Al-substituted Li 7 La 3 Zr 2 O 12 (LLZ:Al) was synthesized via conventional solid state reaction. Different dwell times at sintering temperature of 1200°C led to a varying Li content in LLZ:Al which significantly affected the Li-ion conductivity. Electrochemical impedance spectroscopy and X-ray diffraction were used to characterize the sintered pellets which showed a maximum total ionic conductivity of~3 × 10 −4 S cm −1 at room temperature although the samples were composed of cubic and tetragonal LLZ:Al, wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
58
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 68 publications
(59 citation statements)
references
References 32 publications
1
58
0
Order By: Relevance
“…In this specific case a bulk conductivity of 3.3 × 10 −4 S cm −1 results. This is within the range typically found for such LLZO samples stabilized with aluminium [8,13,[27][28][29][30][31]. However, literature data reveal a large scattering of bulk or total conductivities, and in a separate paper we will show that a substantial variation also exists between numerous nominally identical samples prepared in our labs.…”
Section: Macroelectrode Measurementssupporting
confidence: 80%
See 1 more Smart Citation
“…In this specific case a bulk conductivity of 3.3 × 10 −4 S cm −1 results. This is within the range typically found for such LLZO samples stabilized with aluminium [8,13,[27][28][29][30][31]. However, literature data reveal a large scattering of bulk or total conductivities, and in a separate paper we will show that a substantial variation also exists between numerous nominally identical samples prepared in our labs.…”
Section: Macroelectrode Measurementssupporting
confidence: 80%
“…The highest value found for a Fig. 4 Impedance spectra of two Ti/Pt microelectrodes with different diameter d, and the corresponding fits (dashed line) based on the equivalent circuit shown above [7,8,31]. Plotting the averaged conductivity for every microelectrode diameter shows a clear trend ( Fig.…”
Section: (Dashed Line) Reveals R Spread Values If Thismentioning
confidence: 94%
“…The highly conductive cubic phase have reported that Al dopants play a key role as cubic-phase stabilizers by replacing lithium lattice sites (e.g. 24d, 48 g, and 96 h) [10,11,14,18,23,25] . Although the exact Al sites replacing Li sites are not experimentally clear, it seems quite certain that Al substitution could produce a stabilized cubic phase and provide fast Li-ion conduction.…”
Section: Resultsmentioning
confidence: 99%
“…Any solid electrolytes with fast lithium-ion conduction have been considerable attracted as one of the key technologies for the development of next-generation energy storage systems such as all-solid-state Li batteries, Li-S battery and Li-air battery [1][2][3][4][5] . Various types of lithium-ion-conductive solid electrolytes have been reported, such as layered Li 3 N, Li 14 Zn(GeO 4 ) 4 , Li 1 + x Al x Ti 2-x (PO 4 ) 3 (LATP), Li 3 x La (2/3) −x TiO 3 (LLTO) and Li 7 La 3 Zr 2 O 12 (LLZO) [6] . Among them, garnet-type LLZO has been widely studied as a promising lithium-ion solid electrolyte because of its attractive value of ionic conductivity and its low grain boundary resistance [2] .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation